Phylogeny and morphology of Hirsutella tunicata sp nov (Ophiocordycipitaceae), a novel mite parasite from Peru - Ciancio, A (2013)
The authors gratefully thank Prof. F. Porcelli (University of Bari, Italy) for accession and assistance with a light microscopy facility, Prof. S. Desantis, Dr. G. Accogli (University of Bari), Dr. G. Maglietta (Tecnopolis, Bari) for assistance with SEM and Mr. N. Salatino (IPP, CNR, Bari) for the technical assistance provided. Research partially funded by Bilateral Cooperation Agreement between Consiglio Nazionale delle Ricerche (CNR, Italy) and Consejo Nacional de Ciencia, Tecnologia e Innovacion Tecnologica (CONCYTEC, Peru) and by Project BIOMED (Ministero Politiche Agricole e Forestali, Italy).